Telewizja w kampanii wyborczej – wybrane aspekty - Sopalski, Paweł (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Television has become one of the most significant means of communication during last 50 years. During political campains politicians use a wide range of techniques in order to gain their voters’ support. Debates before elections, polls, announcements on Tv are the most common means used by parties. Developement of technology caused the increase of politicians presence not only in the news but also in the shows.